Quantification of urinary 5-hydroxyindoleacetic acid by in-house nitrosonaphthol reaction compared with nitrosonaphthol micro column chromatography and enzyme-linked immunosorbent assay - Joyce Matie Kinoshita da Silva; Rejane Mattar; Carlos Colaúto; Flair José Carrilho (Sociedade Brasileira de Patologia Clínica, 2014)
The aim of this study was to compare the colorimetric "kit" and enzyme-linked immunosorbent assay (ELISA) methods to quantify urinary 5-hydroxyindoleacetic acid through the Goldenberg's technique, exploring the potential of replacing it. 24-hour urine samples were tested by Goldenberg's assay and compared with kits. The agreement was almost perfect for the comparison of Goldenberg's assay with both colorimetric kit, and with ELISA kit, considering ≤ 7.5 mg/24h normal cutoff value. Therefore, both "kits" would be good alternatives to Goldenberg's technique due to practicality and agreement between values.